Penggunaan analisis korpus melalui aplikasi AntConc dalam penelitian karya sastra - Purwaramdhona, Ananda Bintang (Universitas Mulawarman, 2025)
This article aims to explore how corpus analysis patterns are applied and to demonstrate the practice of using the AntConc application in literary studies. Through a systematic literature review method, this study synthesizes ten studies that utilized AntConc to analyze various literary works, such as poetry and novels. The findings indicate that literary studies using AntConc tend to adopt four reading patterns when approaching literary texts. Furthermore, AntConc features, including word frequency, concordance, collocation, and keyword analysis, can assist researchers in identifying, analyzing, and interpreting thematic patterns, discourses, and narrative structures in literary corpora, provided the objects of study are in written form and convertible into text format (txt). This study is expected to encourage researchers to engage in digital humanities and corpus-based literary research, which can begin with the use of AntConc, particularly in the exploration of Indonesian literary works that remain underexplored.